(untitled) (Global Journal of Management and Business Research, 2016)
This study explains the factors that have an affect on employee job satisfaction within an organization. In addition, this study clarifies the relationship between the work environment and job satisfaction within an organization. This paper demonstrates the importance of attaining job satisfaction through creating a positive workplace. Also, the research illustrates the role of job satisfaction in an organization’s performance. The conclusion of this study shows that working conditions, salary and compensations, fairness, respect from co-workers, and the relationship with supervisors have an overall impact on job satisfaction among an organization’s employees.